NMR and molecular modeling evidence for a G.A mismatch base pair in a purine-rich DNA duplex. - Li, Y (1991)
1H NMR experiments indicate that the oligomer 5'-d(ATGAGCGAATA) forms an unusual 10-base-pair duplex with 4 G.A base pairs (underlined) and a 3' unpaired adenosine. NMR results indicate that guanosine imino protons of the G.A mismatches are not hydrogen bonded but are stacked in the helix. A G----I substitution in either G.A base pair causes a dramatic decrease in duplex stability and indicates that hydrogen bonding of the guanosine amino group is critical. Nuclear Overhauser effect spectroscopy (NOESY) and two-dimensional correlated spectroscopy (COSY) results indicate that the overall duplex conformation is in the B-family. Cross-strand NOEs in two-dimensional NOESY spectra between a mismatched AH2 and an AH1' of the other mismatched base pair and between a mismatched GH8 and GNH1 of the other mismatch establish a purine-purine stacking pattern, adenosine over adenosine and guanosine over guanosine, which strongly stabilizes the duplex. A computer graphics molecular model of the unusual duplex was constructed with G.A base pairs containing A-NH2 to GN3 and G-NH2 to AN7 hydrogen bonds and B-form base pairs on both sides of the G.A pairs [5'-d(ATGAGC)]. The energy-minimized duplex satisfies all experimental constraints from NOESY and COSY results. A hydrogen bond from G-NH2 of the mismatch to a phosphate oxygen is predicted.